Using Mathematical Modeling to Motivate the Study of Polynomial Functions - Bouchat, Rachelle; Barnard, Kristen (Ohio Journal of School Mathematics, 2022)
The authors show how the online graphing tool Desmos can be used to motivate the study of polynomial end-behavior through the use of mathematical modeling of data sets.